Performance evaluation of campus network involving VLAN and broadband multimedia wireless networks using OPNET modeler - Dhurgham Abdulridha Jawad Al-Khaffaf; Mohammed G. Al-Hamiri (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Modern technology is essential for all healthy, economic, and educational sectors. Using modern technology involves high-performance networks in terms of quality of service (QoS) parameters such as delay, throughput, bandwidth, and security. A campus network involves wire and the wireless environment with and without virtual local area network (VLAN) technology has been simulated using optimized network engineering tools (OPNET). The simulation model includes four scenarios that involve heavy-loaded File transfer protocol (FTP) and web browsing applications with two logical groups of users. The simulation results show that the VLAN overcome LAN networks in terms of bandwidth and security. This has been done by reducing the throughput in both sending and receiving levels to the confidential servers. The VLAN has also reduced the broadcast domain which results in a high-power efficiency. Moreover, the VLAN network technology has been proved to have lower values of delay in transferring files and packets than LAN network technology. In addition, VLAN technology generally has been decreased values of throughput regardless of the way of connection between servers and workstations. This, in turn, allows taking advantage of wireless connection features in terms of flexibility of installation and speed of configuration.